Screening of natural phenazine producers for electroactivity in bioelectrochemical systems. Issue 3 (26th December 2022) - Franco, Angel; Elbahnasy, Mahmoud; Rosenbaum, Miriam A.
Abstract: Mediated extracellular electron transfer (EET) might be a great vehicle to connect microbial bioprocesses with electrochemical control in stirred‐tank bioreactors. However, mediated electron transfer to date is not only much less efficient but also much less studied than microbial direct electron transfer to an anode. For example, despite the widespread capacity of pseudomonads to produce phenazine natural products, only Pseudomonas aeruginosa has been studied for its use of phenazines in bioelectrochemical applications. To provide a deeper understanding of the ecological potential for the bioelectrochemical exploitation of phenazines, we here investigated the potential electroactivity of over 100 putative diverse native phenazine producers and the performance within bioelectrochemical systems. Five species from the genera Pseudomonas, Streptomyces, Nocardiopsis, Brevibacterium and Burkholderia were identified as new electroactive bacteria. Electron discharge to the anode and electric current production correlated with the phenazine synthesis of Pseudomonas chlororaphis subsp. aurantiaca . Phenazine‐1‐carboxylic acid was the dominant molecule with a concentration of 86.1 μg/ml mediating an anodic current of 15.1 μA/cm 2 . On the other hand, Nocardiopsis chromatogenes used a wider range of phenazines at low concentrations and likely yet‐unknown redox compounds to mediate EET, achieving an anodic current of 9.5 μA/cm 2 . Elucidating the energetic and metabolic usage of phenazines in these and other species might contribute to improving electron discharge and respiration. In the long run, this may enhance oxygen‐limited bioproduction of value‐added compounds based on mediated EET mechanisms. Abstract : We here investigated the potential electroactivity of over one hundred putative diverse native phenazine‐producers to provide a deeper understanding of the ecological potential for the bioelectrochemical exploitation of phenazines. From 104 tested strains, two showed an outstanding performance for mediated extracellular electron transfer in our BES: P. chlororaphis subsp. aurantiaca and N. chromatogenes .